Bahasa Inggris - Susanti, Ernita; Lutfiani, Silvia; Maulidah, Rifa'atul (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
Problem-solving ability is crucial for students to face 21st-century challenges, especially in physics education, where many concepts are abstract. Despite its importance, students' problem-solving skills in elasticity are often low due to teacher-centered approaches and insufficient use of problem-solving models. This study aims to evaluate the impact of the IDEAL Problem-Solving model on students' problem-solving abilities concerning elasticity material. The research method and design were quasi-experiments with a nonequivalent posttest-only control group design. Analysis revealed outstanding implementation of the IDEAL model, with normality and homogeneity tests supporting the sample's suitability. The t-test (α = 0.05) confirmed that the IDEAL model significantly enhanced problem-solving skills in elasticity. The findings suggest that adopting student-centered models like IDEAL can improve learning outcomes and problem-solving abilities and provide a basis for further research on similar models in other educational contexts.